Effect of injection strategy optimization on PCCI combustion and emissions under engine speed extension in a heavy-duty diesel engine. (15th January 2023) - Lu, Yingying; Fan, Chao; Chen, Yufeng; Liu, Yize; Pei, Yiqiang
Graphical abstract: Highlights: Proper injection strategy should fully utilize the chamber shape to enhance mixing. Retarding single injection timing can increase the indicated thermal efficiency. Two injection strategy can increase fuel-oxygen mixing time and enhance premixing. Optimized injection strategy can decrease NOx and soot and increase the ITEg . Multiple injection strategy prolongs the duration of in-cylinder turbulent motion. At high speed, multiple injections help decrease soot and increase the ITEg . Abstract: To mitigate the consequent emissions of greenhouse gases and to conform to increasingly strict vehicle emission requirements, experiments and numerical simulation were used to study effects of multiple injection strategy on premixed charge compression ignition (PCCI) combustion and emissions under speed extension in a heavy-duty diesel engine fueled with diesel. As the speed increases, the injection duration is prolonged, the injection rate is decreased, the fuel-oxygen mixing degree is decreased. In order to enhance fuel-oxygen mixing, the injection timing of single injection should firstly be optimized to fully utilize the shape of the chamber. Compared with single injection, the double injections can increase the mixing time, the optimized multiple injections can further increase the mixing time, making the premixing more sufficient and the combustion more complete. Compared with double injections, the optimized multiple injection strategy used in this paper adds a short pulse pilot injection before the main injection, which prolongs the duration of turbulent motion in the cylinder, and enhances the mixing rate of the main injection fuel and air. Results reveals that for single injection with injection timing of −15°CA ATDC, at low speed, through optimizing the injection strategy, the NOx and soot emissions are reduced by 38.5% and one order of magnitude, respectively, and the gross indicated thermal efficiency (ITEg ) is increased by 8.66%; at medium speed, by optimizing the injection strategy, the NOx and soot emissions are reduced by 59.3% and 70.4%, respectively, and the ITEg is increased slightly by 0.33%; at high speed, by optimizing the injection strategy, the soot emission is decreased significantly, the NOx emissions and the ITEg are increased slightly. It was found that with the increase of speed, the effect of multiple injection strategy on the ITEg and emissions is gradually increased, and the optimization effect of multiple injection strategy is more obvious than that of low speed.